Distress and psychopathology among Sudanese patients with type 2 diabetes mellitus and its relation to glycaemic control - Mirghani, Hyder O. (J Taibah Univ Med Sci, 2017)
OBJECTIVES: The link between diabetes control and depression is contradictory and inconsistent. Emotional distress is a single and continuous characteristic that has two primary components: content and severity. This finding could provide a link between major depression, diabetes distress, and depression symptoms. In the present study, we aimed to investigate the relationship between depression and diabetes distress and glycaemic control. METHODS: This cross-sectional descriptive study was conducted at a diabetes centre in Omdurman, Sudan, from June to August 2016. Eighty-nine patients with type 2 diabetes and 29 control subjects for psychopathology were interviewed using an English version of the structured 12-item diabetes distress general health questionnaire. Glycaemic control was assessed by measuring glycated haemoglobin in a blood sample drawn from each participant. RESULTS: Eighty-nine diabetic patients and 29 age- and sex-matched controls compose the study cohort. As many as 87.6% of diabetic patients scored >3 for diabetes distress, and psychopathology was reported in 78.8% of diabetic patients vs. 21.2% in control subjects. Emotional burden was most correlated among the components of diabetes distress followed by the physician-related domain. HbA1c level was related to the emotional burden and regimen-related domains of diabetes distress (P-value <0.05). No relationship was evident among other distress domains, psychopathology, or the duration of diabetes. CONCLUSION: Diabetes distress and depression are prevalent among Sudanese diabetic patients. Glycated haemoglobin level was related to the emotional burden of diabetes distress and the regimen-related domain but not to depression or diabetes duration.